2015
DOI: 10.4236/jep.2015.68080
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Extreme Physical, Biological and Chemical Patterns in the Dynamics of Aquatic Ecosystem

Abstract: This study is a part of the research in monitoring systems of environmental impacts in coastal regions in order to develop trophic dynamic models to be used in the aquatic systems management. Meteorological influences in the variability of the nutrients, larvae concentration, dissolved oxygen (DO) and chlorophyll a were investigated in a region where upwelling occurs. Extreme seasonal variations of reanalysis, QuikSCAT, and surface stations from the southeast coast of Brazil, as well as, surface seawater data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…In this study, six groups of larvae were found: ascidians, cirripedians, decapods, bivalves, Mytilidae, and polychaetes. Comparatively, on the island of Cabo Frio, which is located near the lagoon, nine groups of larvae were found including Ostreidae, Isognomonidae, and Bryozoa, which were absent in Araruama lagoon (Oliveira et al, 2015). Cirripedia larvae were the most representative group in terms of abundance in the present work, but in Fernandes et al (2012) and Oliveira et al (2015), the larvae of Mytilidae were found to be just as abundant as Cirripedia.…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, six groups of larvae were found: ascidians, cirripedians, decapods, bivalves, Mytilidae, and polychaetes. Comparatively, on the island of Cabo Frio, which is located near the lagoon, nine groups of larvae were found including Ostreidae, Isognomonidae, and Bryozoa, which were absent in Araruama lagoon (Oliveira et al, 2015). Cirripedia larvae were the most representative group in terms of abundance in the present work, but in Fernandes et al (2012) and Oliveira et al (2015), the larvae of Mytilidae were found to be just as abundant as Cirripedia.…”
Section: Discussioncontrasting
confidence: 51%
“…The microalgal bloom influences the enrichment of the pelagic trophic webs in the region, favoring the upper trophic levels [3,11]. In general, the upwelling production in the region is described according to a conceptual model based on three sequential phases: first is the upwelling phase itself, which brings cold, nutrient-rich water to the mixed layer [3,12,13]. The second is called the productive phase, when the water temperature rises coincident with an increase in the availability of dissolved nutrients, thus fueling primary production and phytoplankton biomass [14].…”
Section: Introductionmentioning
confidence: 99%